2017
DOI: 10.1016/j.bpj.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Near-Membrane Refractometry Using Supercritical Angle Fluorescence

Abstract: Total internal reflection fluorescence (TIRF) microscopy and its variants are key technologies for visualizing the dynamics of single molecules or organelles in live cells. Yet, truely quantitative TIRF remains problematic. One unknown hampering the interpretation of evanescent-wave excited fluorescence intensities is the undetermined cell refractive index (RI). Here, we use a combination of TIRF excitation and supercritical angle fluorescence emission detection to directly measure the average RI in the 'footp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Recent studies have reported differences in the refractive index (RI) among subcellular components, i.e., nuclei have a lower refractive index than cytoplasm 29 , and the mitochondria, lysosomes and endoplasmic reticulum have their own unique RIs 3032 , respectively. In addition to intracellular RI differences, cell type dependent differences 33,34 and cell state dependent differences 34,35 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported differences in the refractive index (RI) among subcellular components, i.e., nuclei have a lower refractive index than cytoplasm 29 , and the mitochondria, lysosomes and endoplasmic reticulum have their own unique RIs 3032 , respectively. In addition to intracellular RI differences, cell type dependent differences 33,34 and cell state dependent differences 34,35 have also been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TIRFM, SAFM can also provide good optical sectioning capacity and high SBR, which has been applied to highly sensitive biosensing, cell adhesion and motility quantification, plasma membrane association and protein diffusion measurement, and near‐membrane refractometry implementation . In addition, SAFM can be combined with existing SMLM methods to perform 3D super‐resolution imaging .…”
Section: Methods For Axial Srfmmentioning
confidence: 99%
“…In summary, SAFM has superior performance, but greater system complexity than TIRFM. Combining these two methods, i.e., using TIRFM for excitation and SAFM for detection, allows further improvement of the optical sectioning capacity …”
Section: Methods For Axial Srfmmentioning
confidence: 99%
“…However, although the lateral resolution and axial optical sectioning can be of the order of, respectively, 220 and 100 nm (18), the stage-scanning requirement makes image acquisition too slow for imaging near-membrane dynamics in live cells. 2) as a full-field technique, either with a resolutioncompromising aperture disk (30) or else in the resolution-preserving vSAF variant (13,31,40), SAF microscopy is a simple, cheap, and less alignmentdemanding whole-field alternative to TIRF. Additionally, no laser source is needed.…”
Section: Saf Applications With Aperture Filteringmentioning
confidence: 99%
“…We advocated the use of SAF in conjunction with TIRF (13), particularly when using TIRF in the prismless, objective-type configuration. Here, SAF can help to remove impurities, imperfections, and unknowns associated with the passage of the laser beam close to the limiting NA of the objective and those resulting from conjugate image planes inside the microscope body (4,40). Also, contrary to the earlier discussed case of SAF with EPI illumination, the combined excitation and emission optical sectioning result in a better surface selectivity of fluorescence detection.…”
Section: Saf Applications With Aperture Filteringmentioning
confidence: 99%